(untitled) (Revista Contexto & Saúde, 2025)
Objective: To verify the effects of supervised physical training after hospitalization for COVID-19. Methods: Quasi-experimental study with 17 patients referred to the physiotherapy outpatient clinic of a public hospital in Goiânia, Goiás, Brazil after hospitalization for COVID-19. They were evaluated before and after 18 sessions of supervised physical training. A form with sociodemographic and economic data, six-minute walk test, one-minute sit-to-stand test, manovacuometry, Modified Medical Research Council, London Chest Activity of Daily, post-COVID-19 functional status scale and the Short Form Health Survey were used. For continuous variables, mean, standard deviation or median with 25th and 75th percentiles were used. For categorical variables, frequencies were used. The distribution was tested by Shapiro Wilk. For comparison, the paired t-test and Wilcoxon tests were used. The significance level was 5%. Results: There was an increase in the distance walked (392.5 ± 105.9 vs 484.7 ± 95.4 m, p<0.001), in the number of repetitions in the sit-to-stand test (16.0 vs 21.5, p<0.001), in the maximum inspiratory pressure (100 vs 110, p=0.005) and in all domains of quality of life (p<0.001). Dyspnea reduced in the Modified Medical Research Council from grades two, three, four (10 patients) to zero and one (17 patients) and in the London Chest Activity of Daily from 25.8 ± 11.2 to 15.6 ± 4.5 points (p<0.001). Conclusion: Supervised physical training improved functional capacity and quality of life, in addition to reducing dyspnea during daily activities and increasing maximum inspiratory pressure.